The Influence of The Addition of Seagrass Litter Powder to The Compressive Strength and Water Absorption ff Eco-Brick - Farida Huriawati; Nurul Kusuma Dewi (JURNAL PERIKANAN DAN KELAUTAN, 2017)
This research is made to knowing the influence of adding amount of seagrass to amountof sand on the compressive strength and the Eco-concrete bricks’s water absorbtion. Themethods used in this research is experiment with a sample of Eco-concrete bricks (20 x10 x 6) cm in adding 4 variation amount of seagrass . the first variation is without addingamount of seagrass (0%), second adding 5%, third adding 15%, and the fourth is adding25%. The examination compressive strength and water absorbtion is do to Eco-concretebricks 28 days age with ten times repetition and take the average number. The result ofthis examination show the number of compressive strength for each variation are 12.102MPa without adding amount of seagrass (0%), 11.011 MPa adding 5%, 7.6044 MPaadding 15%, and 5.3872 MPa adding 25%. The data for examination of water absorbtionare 12.439% without adding amount of seagrass (0%), 13.81% adding 5%, 15.215% adding 15%, and 16.019% adding 25%. The conclution is the more concentration adding amount of seagrass the less number of Eco-concrete bricks’s compressive strength andotherwise the less concentration adding amount of seagrass the less number of Ecoconcretebricks’swaterabsorbtionpower.Keywords : compressive strength, eco-concrete bricks, seagrass, water absorption